Green behavior and corporate social responsibility in Asia - Quoquab, Farzana; Mohammad, Jihad (Emerald Publishing Limited, 2019)
In recent years, the issues of sustainability, green behavior and corporate social responsibility have become a growing global concern. This increased concern for environmental welfare has started to affect the way marketers, managers and policy makers think and organize their businesses. In Western culture, there has been widespread discussion on green related issues; however, different cultures are at an earlier stage in embracing this global change.Green Behavior and Corporate Social Responsibility in Asia seeks to apply this discussion to Asian culture, using case studies that reflect the reaction, response, managerial problems and success of seven Asian countriesIndia, Malaysia, Turkey, Brunei, Iran, Pakistan and Sri Lankain adopting green concepts. These concepts include: green organizations; eco-tourism; food loss and waste; recycling-reuse; waste management practice; green space; the plastic-bag free campaign; care for animals; and, corporate social responsibility.The cases outlined in this book illustrate how numerous companies and organizations operating in Asian countries incorporate green marketing and green management related concepts and issues into their strategy. It will appeal to researchers and practitioners, working in the fields of consumer behavior, human resource management, organizational behavior and sustainability.- Resumé vydavatel
Includes index.
Keywords: společenská odpovědnost firem -- Asie; corporate social responsibility -- Asia; elektronické knihy; sborníky; electronic books; papers of several authors